The "Museum" magazine in the discussion on the educational tasks of the school at the turn of the 19th and 20th centuries - Elżbieta Dolata (Lubelski Rocznik Pedagogiczny, 2020)
At the turn of the 19th and 20th centuries, in Europe, there was a heated discussion about the concept of teaching and upbringing. Pedagogy of this period was dominated by the ideas of naturalism and individualism, which in turn contributed to the changes in the education system. A wide range of people involved in educational issues discussed the shape of the school at that time. On Polish soil, pedagogical journals became an extremely important forum for the exchange of views on education, culture and education. This was the place where the views of the representatives of the “new education” and the traditional school clashed. The Galician magazine „Museum” joined the ongoing discussion about the school. It was a monthly magazine that was published in Lviv between 1885 and 1939 as an organ of the Society of Teachers of Higher Education and was addressed to people connected with secondary education. The article contains conclusions from the analysis of the content of articles concerning the educational tasks of the school, which appeared in the whole period of publishing the „Museum”. The discussion in the magazine focused on a few thematic areas. Most frequently, issues related to the organizational model of schools were raised, innovative concepts of education were discussed and the role of teachers in the process of teaching and education was discussed. The analysis carried out allows us to conclude that the authors of the texts published in the „Museum” magazine have joined in the discussion about the school with great involvement. It can also be said that the „Museum” acted as a representative of innovative concepts of upbringing. It inspired to undertake modernization of the teaching and upbringing process, with reference to foreign models. It played an enormous role in the popularization and adaptation of Western European pedagogical thought to the Polish conditions. It acquainted Polish teachers with its achievements and directions of development, contributing to a better understanding of the role of education in the development of societies.